Is benzoyl peroxide detectable under physiological conditions in orthopaedic cement?. (30th April 2021) - Steiner, Oliver; Melanie, Komaz; Walter, Goessler; Peter, Thomas; Klaus-Dieter, Kühn
Background: Until today, benzoyl peroxide (BPO) as a potential polymethyl methacrylate (PMMA) cement allergen is the subject of controversial discussion. Question/Purposes: Few cases have been reported in literature and ought to be seen critically. To address this issue, the present study aims to determine BPO and their degradation products biphenyl (BP) and benzoic acid (BA) within hardened cement as well as their elution from cement. Methods: Six ordinary cements characterised by different BPO: DmpT ratio were chosen for the study. Subsequently, cements were tested in-vitro under destructive, physiologic and non- physiologic conditions. Results: BPO was not detectable under destructive and physiological conditions. Cements with a N, N-Dimethyl-para-toluidine (DmpT) surplus contained lower BPO, BP and BA concentrations compared to cements with BPO surplus. Conclusions: Furthermore, the ratio of DmpT:BPO had an impact on the turnover of BPO and its degradation products. Clinical Relevance: Moreover, BPO and BP elution under physiological conditions was not detectable (<0.1 μg/mL in saline solution at a ratio of 1+9 cement to saline solution), calling into question whether BPO is relevant as PMMA cement allergen.